Effect of the Pancaniti Learning Model Assisted by Flashcard Media and a Simple Biogas Project on the Science Literacy of Elementary School Students - Leni Nurhafidah; Afridha Laily Alindra; Dania Widia Cahyani; Yuhaniz Aqila; Nurlaila Ramadhan; Mochamad Ilham Abdillah; Caroline Glorya Manurung (BIOCHEPHY: Journal of Science Education, 2026)
Science literacy among Indonesian elementary school students remains below international benchmarks, while locally grounded instructional approaches that integrate sustainability education are still limited. This study investigated the effect of the Pancaniti learning model, a five-stage pedagogical framework based on Sundanese values, combined with flashcard media and a simple biogas project, on fifth-grade students’ science literacy. A one-group pre-test–post-test quasi-experimental design was conducted with 32 Grade 5 students at SDN Purwamekar selected through purposive sampling. Science literacy was measured using three PISA-aligned indicators: identifying scientific problems, explaining scientific phenomena, and using scientific evidence. Data analysis employed the Wilcoxon Signed-Rank Test due to non-normal post-test data. Results showed a significant improvement in science literacy, with mean scores increasing from 6.44 to 8.44 (Z = ?4.112, p < .001) and a large effect size (r = 0.727). The overall N-Gain was 0.58 (moderate), with the highest gain in using scientific evidence (0.72; high). These findings indicate that the Pancaniti model effectively enhances elementary students’ science literacy.